Problems of Weavers Cooperative Societies in Odisha - A Critical Analysis - Shradhanjali Mohapatra (Indian Journal of Extension Education, 2013)
India is a land of handicrafts and handlooms. At the end of the Tenth five year plan the handicraft sector employed 67.70 lakh persons. Again with about 35 lakh handlooms, the handloom sector provided employment to 65 lakh persons, of which, 61 per cent were women. Thus handlooms and handicrafts sectors are not only employment intensive, being second only to agriculture, but also have huge social importance, in view of the fact that they cater to the economically as well as socially weaker sections. India is estimated to have around 2682 handicrafts and 491 handlooms clusters where Orissa covers 272 numbers. of handicrafts and 30 numbers of handloom clusters. The total handloom weavers and allied worker in India is 43.31(2009-10, handloom census) against the 65.50 lakh(1995-96, handloom census). In India nearly 27.83 lakh handloom households are engaged in weaving and allied activities, out of which 87 per cent are located in rural areas and remaining 13 per cent in urban areas. The majority (82 %) of handloom working households are weaver households, which means that at least one member of every such household is engaged in weaving activities. Nearly 14 per cent are allied worker households, three percent are ideal loom household and about one percent are other handloom households having no adult handloom workers.